Characterization of Inertial measurement units using sine-on-random vibration test. (December 2021) - Capriglione, Domenico; Carratù, Marco; Catelani, Marcantonio; Ciani, Lorenzo; Patrizi, Gabriele; Pietrosanto, Antonio; Signorini, Lorenzo; Singuaroli, Roberto; Sommella, Paolo
Abstract: Inertial Measurement Units (IMUs) are currently employed in devices used every day. Among these, there are smartphones, vehicles, drones, robots, and many others. The reliability and dynamical metrological performance represent a critical aspect to be considered for such devices, particularly under the application of vibrations representative of a real situation in which IMUs can operate. For this reason, the authors have proposed a new test plan based on a sine-on random vibration profile characterized by the presence of a sinusoidal component with the addition of a random vibration noise typical of automotive scenarios. The behavior of IMUs under analysis has been analyzed in deep by adopting suitable figures of merit, thus highlighting the impact of the designed stress test on the devices' correct operation.